The utilization of State old age Grant by smallholder farmers in Mopani district, Limpopo Province, South Africa - Dikeledi Petunia Malatji; Michael Akwasi Antwi (Cogent Social Sciences)
Many smallholder farmers based in the rural areas of South Africa are faced with challenges such as lack of veterinary intervention, government support and financial challenges. Hence, social assistance grants such as Old Age Grant are used by smallholder farmers to support their farming activities. However, there is a dearth of information on the extent to which this grant is used by the beneficiaries to carry out their farming activities. This study aims to analyze factors that influence the proportion of the grant used by the Old Age Grant beneficiaries for their cattle farming activities. A total of 53 smallholder farmers who are Old Age Grant beneficiaries were selected to establish how they utilize their grant money and the proportion they use for their cattle farming activities. Furthermore, the current study used Multiple Linear Regression model to analyse data on the demographic and socio-economic factors that influence the Old Age Grant money used by the beneficiaries for their cattle farming activities. The findings of this study identified long queues as the main challenge experienced by the respondents. Moreover, out of ten independent investigated variables, herd size and herder rates appeared to be the only two variables that significantly (P < 0.05) affect the grant money utilized by farmers for their cattle farming activities. These variables can be used by the government to develop programmes and policies that can be used to support smallholder farmers and metamorphose the smallholder farming system to be a more profit-making system.